What explains frontline workers’ views on poverty? A comparison of three types of welfare sector institutions - Blomberg Helena; Kallio Johanna; Kroll Christian; Niemelä Mikko (Wiley-Blackwell Publishing Ltd., 2025)
The study analysed views on poverty among Finnish frontline workers in three welfare sector institutions. Two different institutional logics, universal and selective, and two sectors, the public and the voluntary, were represented. A nationwide survey among social security officials, municipal social workers and diaconal workers was utilised (N = 2,124). The methods applied included factor analysis, the examination of means and multivariate analysis of variance. Frontline workers were found to support structural reasons for poverty regardless of institutional affiliation. Analyses, however, also revealed significant differences between the institutions, but not of the kind expected. Social security officials, working in a universal institution, were less likely to endorse structural factors and more likely to endorse individualistic poverty explanations than were social and diaconal workers. Type of education and personal political ideology, respectively, were also found to be of significant importance for poverty perceptions, independent of institutional logic